Improving Students' Literacy Through Picture Story Books at SDN 1 Gunjan Asri - Aryapangga, Ranung Sakti; Satiawan, Dana; Monika, Ratna; Raehanun, Siti; Herlina, Rosita (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Literacy skills are very important for every individual in helping a person's development. The learning model, especially the independent curriculum, where literacy skills are really needed. Behind the interesting activities presented by teachers and able to be enjoyed by teachers and students, of course the individual abilities of students must be able to develop students' abilities in the learning process. Data from the ministry shows a low figure for students' literacy abilities in Indonesia, especially at the elementary school level, namely 30%. It is very unfortunate indeed to see the fact that the reading ability which should be really needed to support the development of students is actually very low. (PIRLS) once stated that the literacy ability of Indonesian people is at number 41 out of 45 countries and many others. Gunjan Asri Village is a village that has only been expanded for 4 years and is located in a remote area far above sea level. Of course, quality human resources are needed to help develop the region. Judging from the literacy figures in 3 elementary schools of the same level, the figures are low, so this research was carried out to be able to develop the literacy skills of students in Gunjan Asri village.